THE IMPORTANCE OF MULTICULTURAL UNDERSTANDING IN ISLAMIC RELIGIOUS LEARNING - Rizieq, Muhammad Fayadl; As’ad, Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
In the era of rapid globalization, an approach that combines religious dimensions with multicultural understanding becomes very important in the context of Islamic religious learning. This article seeks to understand the positive impact of the integration of multicultural understanding in the process of Islamic religious learning, especially in shaping individual character and contributing to unity in an increasingly heterogeneous society. In an era where cultural diversity is becoming increasingly apparent, it is important to consider Islamic religious learning as something broader than just understanding religious aspects. The integration of multicultural understanding underlies efforts to create an inclusive learning environment, respecting every individual difference. By involving students in a deeper understanding of Islam in a multicultural context, we are able to form a generation that not only has tolerance, but also readiness to face the challenges of an increasingly complex, connected global world. The approach applied involves in-depth research and thorough analysis using relevant theories and supporting data.